PERAN TEMAN SEBAYA DALAM MOTIVASI BELAJAR SISWA SMA - Almala, Aftiy Diya; Cipta, Wine Tiara; Suparmi, Suparmi (Universitas Tanjungpura, 2024)
This article discusses the role of peers in enhancing students' learning motivation at the high school level. This research employs a Literature Review method to analyze the factors influencing students' learning motivation and how peers can affect that motivation. The findings indicate that peers can serve as a source of motivation and encouragement for students, as well as influence their academic performance. Peers not only function as motivators but also play a role in shaping students' attitudes and learning behaviors. The social support provided by peers can enhance students' self-confidence, belief in their abilities, and courage in facing academic challenges. Conversely, negative relationships with peers can divert students' focus from educational goals. This article also discusses the factors influencing peer behavior and interaction, as well as how the characteristics of peer groups can affect the dynamics of interaction and their influence on individuals. This research provides insights into how educational strategies can leverage the role of peers to support students' motivation and academic achievement.